Comparison of Gut Viral Communities in Atopic Dermatitis and Healthy Children - Lu, Xiang; Wang, Hao; Zhang, Jingqi; Jin, Kexin; Ma, Ling; Wang, Yan; Yang, Shixing; Wang, Xiaochun; Shen, Quan; Zhou, Tianji; Xu, Hui; Zhang, Wen (Frontiers in Medicine, 2022)
The immune development and regulation of living individuals are affected by the gut microbiota. The imbalance of gut microbiota is considered to be a key factor that easily induces immune dysregulation and the development of atopic diseases. Atopic dermatitis is a chronic inflammatory skin disease that affects nearly 20% of children. To date, metagenomics research on atopic dermatitis has mainly focused on the skin and gut microbiome. However, here we assessed the composition of the virome in the gut of atopic dermatitis patients and healthy controls for the first time. This study has obtained possible dominant viruses at different viral classification levels. In terms of diversity, the alpha diversity of the patients group was significantly lower than that of the healthy controls group, and the beta diversity of the two groups was significantly different from phylum to family level. These findings provide a new perspective for us to better understand the effect of the gut microecological environment on atopic dermatitis.